Four subunits that are shared by the three classes of RNA polymerase are functionally interchangeable between Homo sapiens and Saccaromyces cerevisiae. - Shpakovski, G.V.; Acker, J.; Wintzerith, M.; Lacroix, J.F.; Thuriaux, P.; Vigneron, M. (Molecular and Cellular Biology, 1995)
Four cDNAs encoding human polypeptides hRPB7.0, hRPB7.6, hRPB17, and hRPB14.4 (referred to as Hs10 alpha, Hs10 beta, Hs8, and Hs6, respectively), homologous to the ABC10 alpha, ABC10 beta, ABC14.5, and ABC23 RNA polymerase subunits (referred to as Sc10 alpha, Sc10 beta, Sc8, and Sc6, respectively) of Saccharomyces cerevisiae, were cloned and characterized for their ability to complement defective yeast mutants. Hs10 alpha and the corresponding Sp10 alpha of Schizosaccharomyces pombe can complement an S. cerevisiae mutant (rpc10-delta::HIS3) defective in Sc10 alpha. The peptide sequences are highly conserved in their carboxy-terminal halves, with an invariant motif CX2CX12RCX2CGXR corresponding to a canonical zinc-binding domain. Hs10 beta, Sc10 beta, and the N subunit of archaeal RNA polymerase are homologous. An invariant CX2CGXnCCR motif presumably forms an atypical zinc-binding domain. Hs10 beta, but not the archaeal subunit, complemented an S. cerevisiae mutant (rpb10-delta 1::HIS3) lacking Sc10 beta. Hs8 complemented a yeast mutant (rpb8-delta 1::LYS2) defective in the corresponding Sc8 subunit, although with a strong thermosensitive phenotype. Interspecific complementation also occurred with Hs6 and with the corresponding Dm6 cDNA of Drosophila melanogaster. Hs6 cDNA and the Sp6 cDNA of S. pombe are dosage-dependent suppressors of rpo21-4, a mutation generating a slowly growing yeast defective in the largest subunit of RNA polymerase II. Finally, a doubly chimeric S. cerevisiae strain bearing the Sp6 cDNA and the human Hs10 beta cDNA was also viable. No interspecific complementation was observed for the human hRPB25 (Hs5) homolog of the yeast ABC27 (Sc5) subunit.